The Development of Institutional Aspects at Health Clinics in Bogor City - Arjuna Rizaldi (MOVE: Journal of Community Service and Engagement, 2022)
Public health development is carried out to achieve optimal health in the community, therefore the Indonesian government makes various efforts to the health service providers in the community. A health clinic is one of the institutions that provide health services to the community, the bigger the clinic, the more complex the institutional activities that are carried out, so they need to create strategies to improve the quality of services in order to improve the image of the clinic in the community. This research was conducted through the stages of observation and interviews which were then compiled using a SWOT analysis. The results found that health clinics are advised to carry out horizontal integration, namely to collaborate with institutions or professionals related to the field of health services.